Analisis Implementasi Pembelajaran Sains Berbasis Kurikulum Merdeka di Taman Kanak-Kanak Kabupaten Cikarang Selatan - Azi Matur Rahmi; Muchammad Arif Muchlisin (Jurnal Ilmiah Wahana Pendidikan, 2022)
Based on the preliminary study, the researcher sees the problem that educators still have difficulties in learning science in the independent learning curriculum, but education must ensure that teaching and learning activities continue according to the level of early childhood development, and with government regulations regarding the renewal of the KTSP curriculum to become an independent curriculum. Basically the curriculum aims to encourage the development of children's potential so that they are ready to take further education. So that this results in less effective science learning where teaching and learning activities are disrupted and the level of achievement of children does not develop according to the level of achievement due to changes in the curriculum. This type of research is mixed research using a quantitative approach. This study uses a mixed method "Explanatory mixed Methods design", namely quantitative and qualitative research methods sequentially. The research method of a combination model or Sequential Explanatory design is a quantitative and qualitative research method sequentially. The results of this study are seen on a quantitative basis, namely science learning with a value of 86.21 and on a qualitative basis, namely observing, classifying, estimating and comparing